Synthesis of N-perfluoroalkyl-3,4-disubstituted pyrroles by rhodium-catalyzed transannulation of N-fluoroalkyl-1,2,3-triazoles with terminal alkynes - Bakhanovich, Olga; Khutorianskyi, Viktor; Motornov, Vladimir; Beier, Petr (Beilstein Journal of Organic Chemistry, 2021)
The rhodium-catalyzed transannulation of N-perfluoroalkyl-1,2,3-triazoles with aromatic and aliphatic terminal alkynes under microwave heating conditions afforded N-perfluoroalkyl-3,4-disubstituted pyrroles (major products) and N-fluoroalkyl-2,4-disubstituted pyrroles (minor products). The observed selectivities in the case of the reactions with aliphatic alkynes were high.
Keywords: pyrrole; transannulation; rhodium carbene; triazole

(untitled) - Gupton, J. T. (Top. Heterocycl. Chem., 2006)

(untitled) - Guernion, N. L.; Hayes, W. (Curr. Org. Chem., 2004)

(untitled) - Bhardwaj, V.; Gumber, D.; Abbot, V.; Dhiman, S.; Sharma, P. (RSC Adv., 2015)

(untitled) - Kaur, R.; Manjal, S. K.; Rawal, R. K.; Kumar, K. (J. Pharm. Chem. Chem. Sci., 2017)

Heterocyclic Chemistry - Joule, J. A.; Keith, M. (John Wiley & Sons, 2010)

(untitled) - Leeper, F. J.; Kelly, J. M. (Org. Prep. Proced. Int., 2013)

(untitled) - Bellina, F.; Rossi, R. (Tetrahedron, 2006)

(untitled) - Davies, H. M. L.; Alford, J. S. (Chem. Soc. Rev., 2014)

(untitled) - Chattopadhyay, B.; Gevorgyan, V. (Angew. Chem., Int. Ed., 2012)

(untitled) - Anbarasan, P.; Yadagiri, D.; Rajasekar, S. (Synthesis, 2014)

(untitled) - Chattopadhyay, B.; Gevorgyan, V. (Org. Lett., 2011)

(untitled) - Kim, C.-E.; Park, S.; Eom, D.; Seo, B.; Lee, P. H. (Org. Lett., 2014)

(untitled) - Rajasekar, S.; Anbarasan, P. (J. Org. Chem., 2014)

(untitled) - Parr, B. T.; Green, S. A.; Davies, H. M. L. (J. Am. Chem. Soc., 2013)

(untitled) - Lei, X.; Li, L.; He, Y.-P.; Tang, Y. (Org. Lett., 2015)

(untitled) - Miura, T.; Hiraga, K.; Biyajima, T.; Nakamuro, T.; Murakami, M. (Org. Lett., 2013)

(untitled) - Miura, T.; Yamauchi, M.; Murakami, M. (Chem. Commun., 2009)

(untitled) - Blastik, Z. E.; Voltrová, S.; Matoušek, V.; Jurásek, B.; Manley, D. W.; Klepetářová, B.; Beier, P. (Angew. Chem., Int. Ed., 2017)

(untitled) - Motornov, V.; Markos, A.; Beier, P. (Chem. Commun., 2018)

(untitled) - Motornov, V.; Beier, P. (J. Org. Chem., 2018)

(untitled) - Motornov, V.; Košťál, V.; Markos, A.; Täffner, D.; Beier, P. (Org. Chem. Front., 2019)

(untitled) - Tichý, D.; Košt́ál, V.; Motornov, V.; Klimánková, I.; Beier, P. (J. Org. Chem., 2020)

(untitled) - O’Hagan, D. (J. Fluorine Chem., 2010)

(untitled) - Han, J.; Remete, A. M.; Dobson, L. S.; Kiss, L.; Izawa, K.; Moriwaki, H.; Soloshonok, V. A.; O’Hagan, D. (J. Fluorine Chem., 2020)

(untitled) - Zhou, Y.; Wang, J.; Gu, Z.; Wang, S.; Zhu, W.; Aceña, J. L.; Soloshonok, V. A.; Izawa, K.; Liu, H. (Chem. Rev., 2016)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Meanwell, N. A. (J. Med. Chem., 2018)

(untitled) - Schiesser, S.; Chepliaka, H.; Kollback, J.; Quennesson, T.; Czechtizky, W.; Cox, R. J. (J. Med. Chem., 2020)

(untitled) - Scattolin, T.; Bouayad-Gervais, S.; Schoenebeck, F. (Nature, 2019)

(untitled) - Zhang, Z.; Yang, S.; Li, J.; Liao, X. (J. Org. Chem., 2016)